Human Biomarker Exposure From Cigarettes Versus Novel Heat-Not-Burn Devices: A Systematic Review and Meta-Analysis. Issue 7 (23rd October 2019) - Drovandi, Aaron; Salem, Saad; Barker, Daniel; Booth, Debbie; Kairuz, Therese
Abstract: Introduction: Novel tobacco products require independent research to assess their safety. This study assessed the current literature for trials comparing levels of biomarkers of exposure (BoE) between conventional cigarettes (CC) and heat-not-burn (HNB) devices. Methods: Ten databases were searched using terms including: "heat not burn, " "iqos, " "teeps, " "mrtp, " "tobacco heating, " and "glo" between January 1, 2010 and August 13, 2019. Randomized controlled trials (RCTs) assessing comparative BoE levels in humans using either CC or novel HNB devices were eligible. BoE were tabulated, and differences between the intervention and control groups were analyzed and combined using a random-effects meta-analysis. Results: Ten nonblinded, RCTs were eligible, involving a total of 1766 participants. Studies regularly reported on 12 BoE (including nicotine). HNB devices assessed included the "IQOS" and "glo" devices and "precursor" (being developed) HNB devices. In comparison to CC, all 12 BoEs assessed were significantly lower for participants assigned to an HNB device. In comparison to smoking abstinence, HNB devices were statistically equivalent for eight BoEs and significantly elevated for four BoEs. Conclusions: This review found that the potential for harm to humans is reduced when using HNB devices compared to CC as indicated by significant reductions in BoE levels. Whilst these results support tobacco manufacturer claims of improved safety, the small number of studies included, limited range of BoE assessed, and involvement of the tobacco industry necessitate further independent research to confirm the HNB devices as being a safer alternative to CC. Implications: This study supports claims made by tobacco manufacturers on the improved safety of HNB tobacco devices in comparison to CC. These novel devices lead to reduced exposure to key biomarkers, which are linked to the health consequences attributed to tobacco use. This has strong implications for international public health as well as further research and policy development relating to the safety aspects and legalities of novel tobacco products.